Serum creatinine to cystatin C ratio as monitoring biomarker in Chinese adult spinal muscular atrophy: a prospective cohort study - Sihui Chen; Qiong Wang; Jiajia Fu; Qianqian Wei; Ruwei Ou; Xiaohui Lai; Xueping Chen; Huifang Shang (Orphanet Journal of Rare Diseases)
Abstract Background The creatinine to cystatin C ratio (CCR) can be used as a biomarker of muscle mass and strength, but no studies have evaluated whether it can be used as a biomarker to monitor the efficacy of treatment with nusinersen in Chinese adults with 5q-associated spinal muscular atrophy (SMA). Methods In this prospective observational study, 28 adult SMA patients were followed for 18 months. Data on motor function and daily activities were collected using the Hammersmith Functional Motor Scale Expanded (HFMSE), Revised Upper Limb Module (RULM), 6-Minute Walking Test (6WMT), and Barthel Index (BI). Serum levels of creatinine (Cr), creatine kinase (CK), and CCR were measured. Spearman correlation and linear mixed models analyzed the relationships between functional scores and laboratory indicators. Results HFMSE scores showed significant improvement at Visit 5 (V5) [+ 1.04 points, p = 0.016), V6 (+ 1.61, p = 0.012), V7 (+ 1.93, p < 0.001), and V8 (+ 1.89, p < 0.001)], while RULM scores improved significantly at V5 (+ 2.00 points, p = 0.024), V7 (+ 2.00, p = 0.032), and V8 (+ 2.00, p < 0.001). The BI also exhibited significant improvement at V7 (+ 5.00, p < 0.001) and V8 (+ 2.50, p < 0.001). The 6MWT did not show significant improvement (p > 0.05). Serum CCR levels were significantly higher than baseline at V5 (+ 4.35 points, p < 0.001), V7 (+ 5.12, p < 0.001), and V8 (+ 6.59, p < 0.001). Cr levels were significantly higher than baseline at V5 (+ 2.39 points, p < 0.001) and V7 (+ 0.90, p < 0.001), while log10 CK levels remained unchanged (p > 0.05). Spearman correlation analysis revealed CCR showed the strongest correlation with functional scores, followed by Cr and log10 CK. Further linear mixed-effect model indicated that after adjusting for covariates, only CCR showed a dynamic positive correlation with HFMSE scores (β = 0.280; 95% CI 0.023–0.537, p = 0.033), while other serum indicators had no correlation with functional scores. Conclusion Long-term use of nusinersen effectively improves motor function and quality of life in adult SMA patients, and CCR may be a better indicator to reflect changes in motor function during treatment compared to other blood biomarkers.